BSCI-22 DETERMINING THE EFFECT OF NOVEL SMALL MOLECULE DRUGS AGAINST THE MIGRATION OF BRAIN METASTASIS INITIATING CELLS (BMICS). (5th August 2022) - Mobilio, Daniel; Kieliszek, Agata; Chafe, Shawn; Venugopal, Chitra; Singh, Sheila
Abstract: BACKGROUND: Brain metastases are secondary tumors that predominantly arise from the spread of lung, skin, and breast cancers. The current standard of care for brain metastases is complete surgical resection, with a median survival of four months. Therefore, there is a dire need to discover new therapies that effectively target brain metastases. To do this, we have identified anti-brain metastasis drugs that specifically target brain metastasis initiating cells (BMICs), a cancer stem cell population that is thought to escape standard therapies and has the ability to leave their primary tumor, seed the brain, and form a secondary brain tumor. Since the migration of the BMICs is essential to the development of brain metastases in patients, the main goal of this study was to determine the effect our anti-brain metastasis drugs have against the migration of lung, skin, and breast BMICs. METHODS: This migration assay utilizes a bi-well silicone structure which effectively establishes a 'wound' healing-like migration assay. BMICs are plated in optimized equal concentrations in each silicone bi-well structure to successfully form two cellular mono-layers that are separated by a middle silicone wall. Once cells adhere to the plate the silicone structure is removed and the area between the two cell populations is imaged over time with an in vitro imaging system. RESULTS: This optimized assay has been used to screen our anti-brain metastasis drugs against the migration of lung, breast, and skin BMICs. Thus far our drugs have been tested against lung and skin BMICs which resulted in a significant decrease in BMIC migration. SIGNIFICANCE: Since brain metastasis arises from the migration of cancer cells to a secondary organ, it is crucial to discover the effect of anti-brain metastasis drugs on BMIC migration prior to the initiation of preclinical animal trials.